Dendritic cell vaccination combined with a conventional chemotherapy for patients with relapsed or advanced pancreatic ductal adenocarcinoma: a single‐center phase I/II trial. Issue 4 (14th May 2021) - Ogasawara, Masahiro; Miyashita, Mamiko; Yamagishi, Yuka; Ota, Shuichi
Abstract: The prognosis of patients with advanced pancreatic cancer is poor. In the present phase I/II study, we have evaluated the safety and the feasibility of Wilms' tumor 1 (WT1) and/or mucin1 (MUC1) peptide‐pulsed dendritic cell (DC) vaccination in combination with chemotherapy in patients with advanced or relapsed pancreatic ductal adenocarcinoma (PDAC). Sixty‐five eligible patients were enrolled. No severe adverse events related to the vaccinations were observed. Objective response rate and disease control rate was 12.3% and 50.8%, respectively. Median progression‐free survival and overall survival were 4.9 and 9.6 months, respectively. DC vaccinations augmented WT1‐ and MUC1‐specific immunity which might be related to clinical outcome. These results indicate that DC‐based immunotherapy combined with a conventional chemotherapy is safe and feasible for patients in advanced stage of PDAC.